Roots too : White ethnic revival in post-civil rights America - Jacobson, Matthew Frye, 1958- (Harvard University Press, 2008)
In the 1970s, white ethnics mobilized around a new version of the epic tale of plucky immigrants making their way in the New World through the sweat of their brow. Although this turn to ethnicity was for many an individual search for familial and psychological identity, Roots Too establishes a broader white social and political consensus arising in response to the political language of the Civil Rights movement.